Southern voices : Biet Dong and the National Liberation Front - Dedrick, Michael Robert; Giebel, Christoph, 1959-; Project Muse. (Lexington : University Press of Kentucky, 2022)
"Southern Voices: Biet Dong and the National Liberation Front presents oral histories from former members of an elite squad of Viet Cong operatives, focusing on their experiences during what is known, in Vietnam, as the American War. Author Michael Robert Dedrick conducted interviews with eight former Biet Dong (the equivalent of Ranger or Special Forces divisions in the US military) and sheds new light on this clandestine group. Best known for their role in the 1968 Tet Offensive, the Biet Dong in the south were organized units hiding in plain sight. Members included farmers, tradespeople, agents, spies, monks, students, intellectuals, and journalists--both young and old, men and women. They were highly patriotic, politically motivated, and very secretive, operating in three-person cells under aliases. Their voices and experiences emerge in this bilingual volume. In recent years, historians have made greater use of Vietnamese primary sources and transformed the study of one of the twentieth century's most controversial conflicts. Ably curated by Dedrick--who also offers his own perspectives as a veteran and peace activist--the firsthand accounts in Southern Voices add a new layer to the history of the Vietnam War and its aftermath"--
Foreword / by Christoph Giebel -- History of Biet Dong -- Saigon Gia Dinh Committee -- Tu Cang, NLF senior officer -- Bay Son, Biet Dong senior officer -- Nguyen Huu Loi, Biet Dong soldier -- Ms. Le Hong Quan, NLF soldier -- Ms. Nguyen Thi Bich Nga, Biet Dong soldier -- Ms. Do Thi Kim Lien, Biet Dong soldier -- Nguyen Duc Hoa, Biet Dong soldier -- Muoi Than, NLF soldier -- Ba Den.
Includes bibliographical references.
Michael Robert Dedrick is vice president of Veterans for Peace Chapter 92, located in Seattle, Washington. He served during the Vietnam War as a US Army analyst and interrogator-linguist in Cholon, Saigon, through the Tet and May Offensives of 1968.
Print version record.
JSTOR
Keywords: Mặt trận dân tộc giải phóng miền nam Việt Nam -- Officials and employees -- Interviews; Mặt trận dân tộc giải phóng miền nam Việt Nam; Soldiers -- Vietnam (Republic) -- Personal narratives; Vietnam War, 1961-1975 -- Personal narratives; Guerre du Viêt-nam, 1961-1975 -- Récits personnels; Military; BIOGRAPHY & AUTOBIOGRAPHY; Southeast Asia; Asia; HISTORY; Soldiers; Employees; Vietnam (Republic); Asian history; History; 1961-1975; Electronic books; interviews; Personal narratives; Interviews; Personal narratives; Interviews; Récits personnels; Interviews